Echocardiography in the time of Covid-19: Ultrasound enhancing agents save time and augment diagnostic information. (1st January 2022) - Sperling, Dylan; Lai, Ashton C.; Bienstock, Solomon W.; Samtani, Rajeev; Beerkens, Frans; Satish, Mohanchandran; Pulaski, Matthew; Edens, Madison; Oates, Connor; Kocovic, Nikola; Buckley, Samantha; Giustino, Gennaro; et al.
Abstract: Background: There are currently no clear guidelines regarding the use of ultrasound enhancing agents (UEAs) with transthoracic echocardiography (TTE) for patients hospitalized with Covid-19. We investigated whether the performance of TTE with UEAs provides more diagnostic information and allows for shorter acquisition time compared to unenhanced TTE imaging in this patient population. Methods: We analyzed the TTEs of 107 hospitalized Covid-19 patients between April and June 2020 who were administered UEAs (Definity®, Lantheus). The time to acquire images with and without UEAs was calculated. A level III echocardiographer determined if new, clinically significant findings were visualized with the addition of UEAs. Results: There was a mean of 11.84±3.59 UEA cineloops/study vs 20.74±8.10 non-UEA cineloops/study (p < 0.0001). Mean time to acquire UEA cineloop images was 72.28±28.18 s/study compared to 188.07±86.04 s/study for non-UEA cineloop images (p < 0.0001). Forty-eight patients (45%) had at least one new finding on UEA imaging, with a total of 62 new findings seen. New information gained with UEAs was more likely to be found in patients with acute respiratory distress syndrome (21 vs 9, p < 0.001) and in those on mechanical ventilation (21 vs 15, p = 0.046). Conclusions: TTE with UEAs required less time and fewer cineloop images compared to non-UEA imaging in patients hospitalized with Covid-19. Additionally, Covid-19 patients with severe respiratory disease benefited most with regard to new diagnostic information. Health care personnel should consider early use of UEAs in select hospitalized Covid-19 patients in order to reduce exposure and optimize diagnostic yield. Highlights: Ultrasound enhancing agents improve diagnostic yield of TTE in hospitalized Covid-19 patients. Diagnostic yield is highest in patients with ARDS and those on mechanical ventilation. UEA images require significantly less time to acquire compared to unenhanced images in this patient population.